DataExplore: An Application for General Data Analysis in Research and Education. Issue 1 (22nd March 2016) - Farrell, Damien
DataExplore is an open source desktop application for data analysis and plotting intended for use in both research and education. It is intended primarily for non-programmers who need to do relatively advanced table manipulation methods. Common tasks that might not be familiar to spreadsheet users such as table pivot, merge and join functionality are included as core elements. Creation of new columns using arithmetic expressions and pre-defined functions is possible. Table filtering may be done with simple boolean queries. The other primary feature is rapid dynamic plot creation from selected data. Multiple plots from various selections and data sources can also be composed using a grid layout. It is thus possible to create publication quality plots. A plugin system allows the addition of features with several plugins already available by default. The program is written in Python and is based on the PyData suite of Python libraries.